The impact of exchange rate towards trade balance: case study in Malaysia, Singapore and Thailand / Mazwina Hanim Abu Bakar - Abu Bakar, Mazwina Hanim (2007)
This study examines the impact of exchange rates on trade balance; the study of three countries that have tighter economic relationship with each other; Malaysia, Singapore and Thailand. While Marshal/-Lerner condition has shown a theoretical relationship between exchange rates and trade balance, previous empirical result evidence gave mixed results on the impact of exchange rates on trade balance. This study examines the trade balance of Malaysia, Singapore and Thailand with exchange rates of USD. JPY and HKD for the sample period of1995 to 2005 using quarterly data. The methodology used in this study is single linear regression in order to analyse the relationship and impact of exchange rate towards trade balance. This study found that exchange rates does give a significant effect and have positive relationship with trade balance in the case of Malaysia. However, in Singapore. the exchange rate has positive relationship but insignificant with trade balance. While in Thailand, the exchange rate has a positive weak relationship with trade balance and it has a weak impact on trade balance.